The impact of ISO 9000 diffusion on trade and FDI: A new institutional analysis - Clougherty, Joseph A; Grajek, Michał (Journal of International Business Studies, 2008)
The effects of ISO 9000 diffusion on trade and foreign direct investment (FDI) have gone understudied. We employ panel data reported by OECD nations over the 1995–2002 period to estimate the impact of ISO adoptions on country-pair economic relations. We find ISO diffusion to have no effect in developed nations, but to positively pull FDI (i.e., enhancing inward FDI) and positively push trade (i.e., enhancing exports) in developing nations.